Disability and Quality of Life of Community-Dwelling Older People - John Siop, Sidiah (2008)
With the increase of life expectancy, more Malaysian will live to old ages. The rapid ageing of the population is leading to an increasing number of disabled older people as disability is associated with increasing age. The study on the prevalence, risk factors for disability and consequences of disability on quality of life is important in the face of the prevailing ageing population. This study assessed disability prevalence and determined factors that predict disability and quality of life among the older people who lived in the community. In this study, Verbrugge and Jette’s model of disablement process has been used as a conceptual frame of reference. Data from the Mental Health and Quality of Life of Older Malaysians Survey (MHQoLOM) were used in this study, which was a national survey conducted from 2003 through 2005 that employed a cross-sectional design. A multi-stage proportional stratified sample of 2980 older persons living in the community in Malaysia, ranging in age from 60 to 104 years were interviewed in the respondent’s home. Statistical procedures for the analyses included descriptive statistics, univariate logistic regression and multivariate logistic regression. The prevalence of disability in at least one of the activities of daily living (ADL) and instrumental activities of daily living (IADL) items was 22.8 percent. Higher prevalence of disability was observed in older women (31%) compared to older men (14.5%). The predictors for disability in men were age, ethnicity, marital status, self-rated health, heart disease, eye disorder and functional limitation. While age, ethnicity, marital status, smoking, self-rated health, respiratory disorders and functional limitation predicted disability in women. Increasing age, being of the other ethnicity compared with the Malay for men and being of Indian ethnicity compared to the Malay for women, being unmarried, poor self-rated health and functional limitations increased the risk of disability in both men and women. The predictors of perceived good quality of life for men were ethnicity, education, income, urban/rural residence, physical activity and self-rated health. Among women, ethnicity, self-rated health and functional limitation predicted perceived good quality of life. Being of Indian and Chinese ethnicity compared to the Malay were associated with reduced perceived good quality of life for both men and women, while being of Bumiputera and other ethnicity compared to the Malay increased the odds of perceived good quality of life among men. Very poor self-rated health compared to excellent self-rated health was associated with lower perceived good quality of life in both men and women. These findings confirmed the independent contribution of risk factors, medical conditions or disease, and functional limitation in the disablement process. The examination of perceived quality of life in relation to the disablement process indicated that risk factors and functional limitation contributed to lower perceived good quality of life. The findings of the study will be relevant for program development to improve functional abilities and to minimize risk factors by early intervention, improve or maintain the quality of life of older people and to promote the use of appropriate health and social resources. Moreover, policy makers and service providers could effectively focus on those factors that are crucial in maintaining functional ability and quality of life of the older Malaysians.